Observation on the Effect of Local Flap Transfer and Sclera Transplantation in Repairing Skin Defect after Eyelid Tumor Operation - Ma, Ying-Hui; Liu, Gang; Yang, Jie (Nepalese Journal of Cancer, 2020)
Introduction: Eyelid tumor refers to the primary eyelid skin and accessory tumors, which not only affects the appearance and vision, and even local infiltration and distant metastasis, thereby threatening life. Surgical resection is the most important and effective treatment, but tumor resection often leads to a wide range of eyelid defects, significantly affecting the shape and function of the eyelid. Therefore, the eyelid defect must be repaired after resection to achieve the purpose of aesthetic appearance and protection of the eyeball. The objective of the study was to analyze the clinical results of local flap transfer and scleral transplantation in repairing skin defect after eyelid tumor operation. Methods: Forty patients with postoperative skin defects of eyelid tumors admitted from December 2008 to December 2018 were taken for analysis and divided into two groups, 20 cases in each group. The control group underwent autologous lip mucous membrane transfer and nearby skin flap, while the experimental group received local skin flap rotation and scleral allograft repair. The clinical effect of repair of the two groups were compared. Results: In the experimental group, the effect of clinical repairs were better, the difference of height of palpebralfissure and the length of palpebral fissure were compared with the control group, which showed statistical significance favoring the experimental group. Conclusion: Local flap transfer and scleral transplantation has better clinical outcome to repair the skin defect after operation of eyelid tumor.